Sensory Pets - Taylor , Katie; beranek, carol; italiona, lee (sweden autumn publishing, 2024)
Engage your baby$1 (Bs senses with this interactive board book, perfect for sensory play. You and your child can explore different textures on every page, with multiple animals to touch, see and hears
Scientific notions
see feel hear move learn
For children aged 3 - 6 years
Keywords: Scientific notions